Associations of maternal fructose and sugar-sweetened beverage and juice intake during lactation with infant neurodevelopmental outcomes at 24 months. Issue 6 (6th October 2020) - Berger, Paige K; Plows, Jasmine F; Jones, Roshonda B; Alderete, Tanya L; Rios, Claudia; Pickering, Trevor A; Fields, David A; Bode, Lars; Peterson, Bradley S; Goran, Michael I
ABSTRACT: Background: Our prior studies revealed that infant somatic growth is influenced by fructose in breast milk, and fructose in breast milk is increased in response to maternal sugar-sweetened beverage (SSB) intake in lactation. It is unknown whether infant neurodevelopmental outcomes are also influenced by maternal SSBs in lactation. Objectives: To determine whether infant cognitive development at 24 postnatal months was influenced by maternal fructose consumption during lactation, and whether this relation persisted after accounting for maternal SSB and juice (SSB + J) intake. Methods: Hispanic mother–infant pairs ( n  = 88) were recruited across the spectrum of prepregnancy BMI. Mothers completed two 24-h dietary recalls at 1 and 6 postnatal months, and reported breastfeedings per day. The Bayley-III Scales of Infant Development were administered at 24 postnatal months to assess infant cognition. Linear regressions were used to examine associations, reported as unstandardized (B) coefficients, 95% CIs, and P values. Results: Mothers consumed 1656 ± 470 kcal, 21.8 ± 12 g fructose, and 2.5 ± 2.6 servings SSBs + J, and reported 6.9 ± 2.1 breastfeedings per day at 1 postnatal month. Controlling for maternal age, prepregnancy BMI, education level, kilocalories, infant age, sex, and birthweight revealed that infant cognitive development scores at 24 postnatal months correlated inversely with maternal fructose consumption at 1 postnatal month (B = −0.08; 95% CI = −0.13, −0.03; P  < 0.01). The association of infant cognitive development scores with maternal fructose consumption was no longer significant after adjustment for maternal SSB + J intake (B = −0.05; 95% CI = −0.10, 0.00; P  = 0.07), whereas maternal SSB + J intake was significant in the same model (B = −0.29; 95% CI = −0.52, −0.05; P  = 0.02). Infant cognitive development scores were not associated with maternal fructose and SSB + J consumption at 6 postnatal months. Conclusions: Our findings suggest that infant neurodevelopmental outcomes at 24 postnatal months can be adversely influenced by maternal fructose intake in early lactation, and this could be attributed to maternal SSB + J intake.